Identification of a bridge-specific intramolecular exciton dissociation pathway in donor–π–acceptor alternating conjugated polymers - Zhaoyong Jiao; Tingting Jiang; Zhongpo Zhou; Chaochao Qin; Jinyou Long; Yufang Liu; Yuhai Jiang (Nanoscale Research Letters, 2021)
Abstract Intramolecular exciton dissociation is critical for high efficient mobile charge carrier generations in organic solar cells. Yet despite much attention, the effects of π bridges on exciton dissociation dynamics in donor–π–acceptor (D-π-A) alternating conjugated polymers remain still unclear. Here, using a combination of femtosecond time-resolved transient absorption (TA) spectroscopy and steady-state spectroscopy, we track ultrafast intramolecular exciton relaxation dynamics in three D-π-A alternating conjugated polymers which were synthesized by Qin's group and named HSD-A, HSD-B, HSD-C. It is found that the addition of thiophene unit as π bridges will lead to the red shift of steady-state absorption spectrum. Importantly, we reveal the existence of a new intramolecular exciton dissociation pathway mediated by a bridge-specific charge transfer (CT′) state with the TA fingerprint peak at 1200 nm in π-bridged HSD-B and HSD-C. This CT′ state results in higher electron capture rates for HSD-B and HSD-C as compared to HSD-A. Depending on the proportion of CT′ state and nongeminate recombination are important step for the understanding of high power conversion efficiencies in HSD-B than in HSD-C. We propose that this bridge-specific exciton dissociation pathway plays an important role in ultrafast intramolecular exciton dissociation of organic photovoltaic material D-π-A alternating conjugated polymers.